Baptism in the medieval canon law - Helmholz, Richard H. 1940- (2013)
The classical statements of the medieval canon law, Gratian's Decretum (ca. 1140) and the Gregorian Decretals (1234) both dealt with baptism. Although a 'theological' subject, baptism had worldly consequences and ist correct performance was thought to require regulation. This article seeks to bring to light the character of the canon law's treatment of baptism by comparing ist treatment with that it applied within the law of marriage, also a sacrament of the medieval church. It surveys and compares the verbal formulas used for both, the standards of legal finality applied to choices made by and for children, the effect of coercion upon the validity of both, the role of parents and the clergy in arranging for and performing the two sacraments, and the common problem of dealing with legal uncertainty about each sacrament's performance and validity. It states the basic rules applied in each case. In all of these areas, the canonists sought to arrive at objective and workable standards, but they turn out to have been more willing to bend somewhat to the subjective expectations of the men and women involved in dealing with marriage than with baptism. The explanation for the differences seems to lie in the unequal value accorded to the two sacraments by the medieval church. Baptism lay at the centre of the church's mission in the world. Marriage did not.
Keywords: Mittelalter; Recht; Geschichte; Taufe; Kirchenrecht; Ehe; Sakramentenrecht